1989
DOI: 10.1139/f89-032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Off-Channel Ponds in the Life Cycle of Coho Salmon (Oncorhynchus kisutch) and Other Juvenile Salmonids in the Coldwater River, British Columbia

Abstract: Off-channel ponds in the upper reaches of the Coldwater River, British Columbia, were major rearing areas for juvenile coho salmon (Oncorhynchus kisutch). Chinook salmon (Oncorhynchus tshawytscha), steelhead trout (Salmo gairdneri), and Dolly Varden char (Salvelinus malma) were generally scarce in the ponds, although they were numerous in the main river. Coho salmon were predominant at "natural" river sites while steelhead trout was the main species at sites with "rip-rap" bank stabilization. Catches of juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 3 publications
5
58
1
Order By: Relevance
“…In addition, at the onset of floodplain and seasonal tributary inundation, the increase in overall available habitat is likely to both reduce competition and lower predation risk (Sommer et al 2001). Greater prey densities in offchannel habitat relative to the main-channel may also improve feeding rates and result in faster growth (Swales and Levings 1989). Rarely have the effects of off-channel habitats on juvenile salmon growth or survival been quantified (Simenstad and Cordell 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at the onset of floodplain and seasonal tributary inundation, the increase in overall available habitat is likely to both reduce competition and lower predation risk (Sommer et al 2001). Greater prey densities in offchannel habitat relative to the main-channel may also improve feeding rates and result in faster growth (Swales and Levings 1989). Rarely have the effects of off-channel habitats on juvenile salmon growth or survival been quantified (Simenstad and Cordell 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the glacially fed Taku River, Murphy and others (1989) found that velocity was a more important factor in habitat selection than turbidity. An increase in the abundance of lower velocity side channels have been shown to be beneficial to juvenile coho (Tschaplinski and Hartman, 1983) and are suspected to be beneficial to juvenile spring Chinook, particularly during high winter flows (Swales and Levings, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The ponds may be connected or disconnected from the main channel depending on the flow. Channel complexity is important to fish because it provides the large variety of habitat types needed at different life stages and seasons for reproduction, rearing, and refuge (Taylor 1988, Swales and Levings 1989, Swales et al 1986, Richards and Cernera 1992, Pearsons et al 1992.…”
Section: Channel Complexitymentioning
confidence: 99%
“…Also, side channel are often more sinuous than the main channel and comprise a variety of habitat features, including complex edges and eddies (Hardin-Davis et al 1990, Richards et al 1992, Everest and Chapman 1972 3. Natural pond area was included as a variable because the ponds offer low-velocity rearing habitat that is next to the main channel that chinook and other salmonids use at various times of the years (Swales and Levings 1989). If these ponds do not have non-native fish (e.g., bass), fish benefit by being separated from predatory fish in the main channel.…”
mentioning
confidence: 99%